Kualitas Konselor Sebagai Penentu Proses Konseling yang Berhasil - Saragih, Nur Afifah Nabila; Hariko, Rezki; Karneli, Yeni (Indonesian Journal of Educational Counseling, 2023)
Counseling is a process of providing assistance to individuals who have problems. The goal is to eradicate and develop individuals who develop optimally so that they can become independent individuals. It takes the figure of a counselor. As a counselor who has quality, a counselor who will be a successful counseling. This research is a qualitative descriptive study. Aims to find out how the quality of the counselor as a companion to the counseling process is successful. Data collection uses the results of interviews, observations and literature studies sourced from various literature both from books and research journals. The research subjects were 3 counseling teachers and 3 students at SMA Negeri 10 Medan. The technique of taking research subjects using a purposive sampling technique. The results can be concluded that the quality of the counselor is a major factor in the success of counseling. The counselor's qualities include being able to understand himself, having knowledge in his field, having good mental health, being warm, honest, self-sacrificing, patient, sensitive, a good listener, honest, to a trusted counselor. So that in this case the counselee's trust in the counselor is formed. This is what will shape the counseling process into successful counseling.